2016
DOI: 10.2196/resprot.6089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Charitable Versus Monetary Incentives on the Acceptance of and Adherence to a Pedometer-Based Health Intervention: Study Protocol and Baseline Characteristics of a Cluster-Randomized Controlled Trial

Abstract: BackgroundResearch has so far benefited from the use of pedometers in physical activity interventions. However, when public health institutions (eg, insurance companies) implement pedometer-based interventions in practice, people may refrain from participating due to privacy concerns. This might greatly limit the applicability of such interventions. Financial incentives have been successfully used to influence both health behavior and privacy concerns, and may thus have a beneficial effect on the acceptance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The design of this study is described in greater detail elsewhere. 27 Briefly, this study was conducted in cooperation with a large Swiss health insurance company that implemented a 6-month pilot initiative to promote physical activity among its insureds from July to December 2015. In June 2015, eligible insureds were randomly assigned to a type of incentive (personal financial, charity financial, or no incentive) and invited via e-mail to participate in the pilot program.…”
Section: Methodsmentioning
confidence: 99%
“…The design of this study is described in greater detail elsewhere. 27 Briefly, this study was conducted in cooperation with a large Swiss health insurance company that implemented a 6-month pilot initiative to promote physical activity among its insureds from July to December 2015. In June 2015, eligible insureds were randomly assigned to a type of incentive (personal financial, charity financial, or no incentive) and invited via e-mail to participate in the pilot program.…”
Section: Methodsmentioning
confidence: 99%
“…We invited insurees via email to participate in our study. On the basis of a previous study in the same population and with a similar recruiting process [60], we expected a participation rate of approximately 3%. We initially sent the invitation email to 10,000 insurees.…”
Section: Methodsmentioning
confidence: 99%
“…The timing, content, and order of quizzes were the same for all individuals, other than the initial quiz timing, which will be discussed in greater detail in the Study Design section. Quizzes were developed to inform and familiarize users about self-regulatory health skills [ 32 ] or stepping stone behaviors (ie, goal setting, tracking, action planning, and barrier identification), skills that have been demonstrated in the past to promote health behaviors [ 31 ]. After completing a health quiz or health risk assessment and immediately earning incentives (US $0.04 to US $1.48 depending on the length, timing, and date of completion of the quiz), users could view relevant health information on partner websites.…”
Section: Methodsmentioning
confidence: 99%
“…In the first few weeks after its launch in 2016, Carrot underwent several important program changes, resulting in a nonexperimental observational study [ 27 ] that can be examined to shed light on factors influencing engagement. Our primary objective was to examine the impact of reducing reward size on engagement to tackle competing predictions: although previous research has suggested that the size of a financial incentive is important for sustained engagement and thus behavior change [ 28 , 29 ], which is consistent with principles of economic rationality, other research [ 30 ] and theory in consumer psychology suggest that the magnitude of the incentive may be somewhat inelastic to size [ 30 - 32 ]. The secondary objectives were to examine whether reward timing, type of reward, and health intervention content influence engagement.…”
Section: Introductionmentioning
confidence: 99%